La hacienda y la conciencia. Las propuestas del confesor del Conde Duque para el saneamiento de las finanzas reales (1625) - Negredo del Cerro, Fernando (Cuadernos de Historia Moderna, 2002)
The influence of the Catholic Church in the economic situation during the Habsburg government in Spain is well known. However, it is no very easy to find examples of this evidence in the historiography. In this article, the author analyses the subject through an unpublished document found in the Biblioteca Nacional (Madrid). The document contains the suggestions of Father Salazar, confessor of Conde-Duque de Olivares. Father Salazar reflects on the reorganisation of royal finances. In his writing, we can read not only economic proposals, but the intention of a member of the Church to transform some political practices and, especially, the system of councils.